Pengaruh Gaya Hidup, Lokasi, dan Kelompok Acuan Terhadap Minat Kunjung Kembali Tujungan Plaza Surabaya - Rahayu Mardikaningsih; Didit Darmawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Every big city has a shopping center as one of the economic activities carried out. In the city of Surabaya, there are various shopping centers that have various target visitors. Tunjungan Plaza Surabaya is the second largest shopping center in Indonesia which has many competitors in the city of Surabaya. For that it is important to always increase visitors every time. For this reason, it is necessary to know the factors that can influence the interest in revisiting, such as lifestyle, location, and reference groups. This study aims to determine the role of lifestyle, location, and reference group on interest in returning. The population of this study is Surabaya residents who visited Tunjungan Plaza Surabaya more than twice in the past 3 years. The sample used is 100 respondents. This study uses multiple linear regression. The results of the study show that lifestyle plays a significant role in the interest in returning to Tunjungan Plaza Surabaya. Furthermore, location also has a significant and positive impact on the revisiting to Tunjungan Plaza Surabaya. The reference group also has a significant impact on the revisiting to Tunjungan Plaza Surabaya